The basis of patient resistance to opportunistic discussions about weight in primary care - Tremblett, M; Webb, H; Ziebland, S; Stokoe, E; Aveyard, P; Albury, C (Taylor & Francis, 2023)
Clinicians expect that talking to patients with obesity about potential/future weight loss will be a difficult conversation, especially if it is not the reason that a patient is seeking medical help. Despite this expectation, many governments ask clinicians to take every opportunity to talk to patients about weight to help manage increasing levels of obesity. Although this is recommended, little is known about what happens in consultations when clinicians opportunistically talk to patients about weight, and if the anticipated difficulties are reality. This paper examines displays of explicit patient resistance following opportunistic weight-loss conversations initiated by GPs. We analyzed audio recordings and transcribed them for conversation analysis. We focused on the precursors of explicit resistance displays during opportunistic weight loss discussions, the format of the resistance, and the ways it was managed by GPs. We found relatively few instances of explicit resistance displays. When it did occur, rather than be related to the opportunistic nature of the advice, or the topic of weight itself, resistance was nuanced and associated to the sensitivity of the GPs managing unknown patient levels of awareness of weight loss benefits, or prior efforts to lose weight. Clinicians tended not to challenge this resistance from patients, and we suggest this tactic may be acceptable to patients and help foster the long-term collaborative relationships needed to tackle obesity. Data are in British English.